Philosophy and Music Education: A Research on Ethical Issues - Wolffenbüttel, Cristina Rolim (2022)
The growth of research in music education in Brazil, together with the advancement of ethical care in research, led to this research, which aimed to investigate aspects related to ethical care in research in music education in Brazil, based on Resolution CNS No. 510/2016 (BRAZIL, 2016). Data were collected via the Internet, in the ABEM Journal, with a time frame from 2016 to 2022. As a result, five articles were found. It is understood, in this sense, that there is room for the growth of investigations in music education and that deal with research ethics. Despite the advancement of legislation regarding research ethics, as well as the need for investigations in music education to also consider these issues in their data collection and analysis, the theme has been little considered in the methodological procedures.